GM2-Activator Protein. Issue 1 (January 2015) - Potprommanee, Laddawan; Ma, Haou-Tzong; Shank, Lalida; Juan, Yi-Hsiu; Liao, Wei-Yu; Chen, Shui-Tein; Yu, Chong-Jen
<x xml:space="preserve">Abstract</x> Introduction: Effective biomarkers for early diagnosis of lung cancer are needed. A recent study demonstrated that urinary GM2-activator protein (GM2AP) level was increased in lung cancer patients. This study aims to validate the potential application of GM2AP as a biomarker for diagnosis of lung cancer. Methods: Serum and urine samples were obtained from 189 participants (133 patients for treatment naive lung cancer, 26 healthy volunteers for urine, and 30 healthy volunteers for serum). GM2AP level was detected by Western blotting and quantified using enzyme-linked immunosorbent assay (ELISA). The GM2AP expression in tumors and nontumor parts of lung tissues from 143 nonsmall cell lung cancers was detected by immunohistochemical stains. Results: There was an 8.11 ± 1.36 folds increase in urine and a 5.41 ± 0.73 folds increase in serum level of GM2AP in lung cancer patients compared with healthy volunteers (p < 0.0001), achieving a 0.89 AUC value in urine and 0.90 AUC value in serum for the receiver-operating characteristic curves. Both serum and urine levels of GM2AP correlated significantly with pathology stages (urine, p = 0.009; serum, p < 0.0001). Using immunohistochemical, positive expression of GM2AP was found at 83.9% of nonsmall cell lung cancers patients and none in normal tissue. The GM2AP expression was significantly correlated with pathology stage (p = 0.0001). Patients with higher GM2AP expression had shorter overall survival (p = 0.045) and disease-free survival (p = 0.049) than lower GM2AP expression. Moreover, the multivariate analysis suggested GM2AP as an independent predictors of disease-free survival and overall survival. Conclusions: Our study demonstrates that GM2AP might serve as potential diagnostic and prognostic biomarkers in patients with lung cancer.